Persepsi Remaja Terhadap Atribut Sosialibilitas Pada Setting Alun-alun Purwokerto - Yohanes Wahyu Dwi Yudono (Teodolita ( Media Komunikasi Ilmiah di Bidang Teknik ), 2017)
The user's perception of a physical environment is not passive in receiving external stimuli. The stimulus may be a property present in the setting of an environment. The existence of the property in the environment setting is sent from the eye to the brain to be understood and understood by the user based on his experience.    The operational theory of the research is built on the philosophy of rationalism by giving meaning based on sensual, logical, and ethical implications by relating the reality of the object of the research (Noeng Muhadjir, H. Prof. DR (2000). Weismann (1981) about the attributes as independent variables, as well as the theory of Paull A. Bell, et.al (1978) in Sarwono (1995) on the perceptions and theories of Atkinson Rita, L, et al (1983) about internal factors as dependent variables. Using descriptive statistical calculations.    Thus can be formulated about the alleged cause of the emergence of multiple meanings on the phenomenon of the setting of the square of Purwokerto, that is the difference in perception as a result of the function of function in the conception of public space. The difference of perception in question, concerning the internal factors of individuals (users of the square, in this case adolescents) in the form of motivation, hope, and interest of adolescents to the setting of the square.    In this study apply operational theory that was built by basing on Weismann's theory (1981) about the attributes as independent variables, as well as Paull theory. A. Bell, et al (1978) about the perceptions and theories of Atkinson Rita. L, et al (1983) about internal factors as dependent variables. While the method of analysis used in this study is with the calculation of descriptive statistics.    The result of this research is to see the correlation between the perception of adolescent to the attribute of sociability of space gathered on the setting of Purwokerto square. The results of the study showed: adolescent perception toward socialization attributes based on consideration when social interaction can be done by sitting adjacent (between 0 s / d 0,5M) 40,81% and sitting far apart (between 0,5 s / d 1,3M ) 0%.Keywords: Perception, Attributes, Socialization.